In Vitro Evaluation of Ice‐Cold Saline Irrigation During Catheter Radiofrequency Ablation. (23rd July 2014) - SQUARA, FABIEN; MAEDA, SHINGO; ALDHOON, BASHAR; MARGINIERE, JULIE; SANTANGELI, PASQUALE; CHIK, WILLIAM W.; MICHELE, JOHN; ZADO, ERICA; MARCHLINSKI, FRANCIS E.
In Vitro Evaluation of Ice‐Cold Saline Irrigation Introduction Irrigated radiofrequency (RF) catheters allow tissue‐electrode interface cooling, decreasing thrombus risk while enabling higher RF power delivery. The impact of irrigation with ice‐cold saline (ICS) instead of conventional ambient‐temperature saline (ATS) on lesion formation is unknown. Methods and Results We performed 120 RF ablations in vitro on porcine left ventricles, using ICS (<5 °C) or ATS (21 °C) irrigation. For ICS irrigation, the irrigation circuit was cooled externally to maintain delivery of cooled saline at the catheter's tip. We applied 20 g of contact force, and delivered 20 W (irrigation 8 or 17 mL/min) or 30 W (irrigation 17 or 30 mL/min) RF power. Temperatures at tissue‐electrode interface and 3‐mm depth were assessed by fluoroptic probes. Lesion dimensions were assessed. ICS irrigation cooled the tissue‐electrode interface better than ATS (53.9 ± 9.6 °C vs. 63 ± 11.4 °C, P < 0.001). Temperatures at 3‐mm depth were similar at 30 W using ICS and ATS (104.2 ± 9.3 °C vs. 105.8 ± 7.3 °C, P = 0.5), but were cooler at 20 W using ICS (71.3 ± 11.6 °C vs. 100.2 ± 11.9 °C, P < 0.001). This translated into smaller lesions at 20 W with ICS versus ATS. At 30 W with 17 mL/min flow rate, lesions had the same depth with ICS and ATS (4.9 ± 0.8 mm vs. 5.4 ± 0.7 mm, P = 0.13) but were narrower with ICS (7.7 ± 0.8 mm vs. 9.3 ± 1.2 mm, P = 0.001). At 30 mL/min, lesions had the same dimensions. Steam pop rate was similar using ICS or ATS irrigation. Conclusion ICS irrigation more effectively cools tissue‐electrode interface than ATS. This may improve RF safety by potentially decreasing thrombus formation, thus facilitating safe ablation at a low saline volume load. However at lower RF power, ICS reduced lesion size compared to ATS.